PELAKSANAAN MANAJEMEN MICE (MEETING INCENTIVE CONVENTION EXHIBITION) DI HOTEL PANGERAN PEKANBARU - Siregar, Damara Saputra; Achmnes, Syofia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Implementation of MICE management operationalize theoretical concepts inthe book P.Hasibuan Terry GR (2005) that state that the management process consistsof: planning, organizing, actuating, and controlling.Growing MICE industry in Indonesia, including the city of Pekanbaru. CityGoverment continues to initiate Pekanbaru city as MICE city in Sumatera. One of theleading institutions that have a major role in the realization of this idea is thePangeran hotel Pekanbaru. which is a four-star hotel MICE service providers with ahigh number of events.The formulation of the research problem is how the implementation of theMICE management in Pangeran Hotel Pekanbaru. This study uses descriptivequalitative research with census sampling. The data collected with observation,interview and questionnaire.Based on research in the field, the original purpose of the existence of MICEin Pangeran Hotel Pekanbaru is a venue to facilitate and serve each agency ororganization that will organize a MICE event. Implementation of MICE managementhas done well, ranging from the planning stage, organizing, actuating and controllinghas done well. Management process has been carried out in accordance with existingrules and procedures for this purpose so that the company has exceeded the target set.But there are still some factors that affect the implementation of the MICEmanagement in Pangeran hotel Pekanbaru is human resources, infrastructures andmeans of motivation. Still inadequate number of available resources in terms of bothnumber and skill and still very rarely done given training so that skills training andjob performance is still lacking. And also still lack the necessary infrastructure thusaffecting the services provided.Implementation of MICE management in Pangeran hotel Pekanbaru should beimproved so that the achievement of corporate goals can be realized with betterconsidering the high number and complexity of existing competition.Keywords: Management, Hotel, MICE